Relationships between blood concentrations of cadmium, lead, mercury, selenium, and manganese and the risk of chronic kidney disease: a cross-sectional study based on NHANES 2011–2018 - Shenghua Yao; Dan Xu (Archives of Medical Science)
Introduction Currently, knowledge on relationships between blood concen-trations of cadmium, lead, mercury, selenium, and manganese and the risk of chronic kidney disease (CKD) is lacking. The aim of the study was to ex-plore the relationships between blood concentrations of heavy metals and the occurrence of CKD.